Development of an interdisciplinary framework for post-conflict economic recovery of countries within the paradigm of international economic relations - Hramotniev, Vitalii; Buriachenko, Andrii; Obolenska, Tetiana; Logvinov, Pavlo (Technology audit and production reserves, 2025)
The object of research is post-conflict economic recovery as a component of international economic relations, encompassing interactions among donors, recipients, international organizations, and foreign investors. One of the most problematic aspects is the excessive simplification of this phenomenon within technocratic or narrowly disciplinary approaches, which leads to the neglect of political, social, institutional, and cultural factors, as well as the deep-rooted contradictions underlying the conflict. Existing concepts are unable to fully reflect the complexity of the recovery process and the risks of conflict relapse, particularly in conditions of political uncertainty and limited state capacity. The research employed methods of interdisciplinary analysis, content analysis of scholarly sources and normative-institutional documents, critical review of the limitations of current approaches, and inductive generalization for the development of a new conceptual framework. This enabled a systematic comparison of three leading academic approaches – conflict studies, institutional economics, and transition theory – in their interpretations of the key categories: “post-conflict”, “economy”, and “recovery”. As a result, an updated interdisciplinary analytical framework was developed, within which post-conflict recovery is understood as a multidimensional process of transformation unfolding within a space of fundamental contradictions: order / chaos, old / new, justice / injustice. This is due to the fact that the proposed model enables the integration of economic, institutional, and social dimensions, moving beyond the linear logic of reconstruction in favor of a flexible and context-sensitive approach. This framework makes it possible to develop recovery strategies that are adapted to local conditions, enhance trust, legitimacy, and inclusion, and reduce the risks of conflict recurrence. Compared to existing well-known concepts, it offers such advantages as greater adaptability, multidimensionality, and practical relevance for international economic policy in the context of post-conflict transformations and the complex social legacy of war.